ANALISIS SISTEM ANTRIAN UNTUK OPTIMALISASI PELAYANAN TELLER (Studi Kasus pada Bank Negara Indonesia Kantor Cabang Slamet Riyadi Solo) - Nur Ima Fitriani; Sunarso Sunarso; Erni Widajanti (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2020)
This study aims to determine the queuing system for optimization of teller services at Bank Negara Indonesia, Slamet Riyadi Solo Branch Office. The data used in this study is a direct observation of the object of research / observation. The sampling technique uses the Leddy formula because the population cannot be known. The data analysis technique used is manual calculation using the queuing system formulas of many single-stage channels (multiple channel-single phase). The results of this study indicate that teller services for customers using 4 counters are not optimal because ≥ 5 minutes or 31,16 minutes occur at counter 4, while the time to wait in the queue is compared to the company's standardization of 5 minutes, so researchers do calculations using additions become 5 counters and can only get optimal results, namely ≤ 5 minutes or 0,18 minutes occurs at counter 1.